Omne, quod non est ex fide, peccatum est the relevance of good faith in canonical transactio - Parini Vicenti, Sar (Vergentis, 2016)
It is quite clear that there is a canonical foundation underlying the institute of transactio. Indeed, a compromise is often reached when a dispute has already entered the litigation phase, and as such legal doctrine tends to separate the economic aspect from the ethical aspect in its interpretation. Though the Church has a necessarily imperfect system of legal sanctions at its disposal, over the centuries it has in fact played a fundamental role in the ethical aspect of compromise. Indeed, the Gospel teaches that every human relationship must be based on concordia, as concordia mater est unitatis: if parties have ignored such morals and are about to litigate, or have already started legal proceedings, the Church must exhort them to settle the dispute. This article aims to examine the relevance of two of the essential requirements of transactio - namely lis and res dubia - within the Decretals (X 1.36. 1-11 de transactionibus). The framework of this analysis is provided by the tenet Effectus transactionis est, ut ei stetur, which sanctions the effectiveness of transactio as a juristic act. The goal is to evaluate how the uncertainty of legal proceedings relates to the principle of good faith in canon law.